Parent–child interaction therapy (PCIT) with families of children with autism spectrum disorder. (December 2022) - Vess, Sarah F.; Campbell, Jonathan M.
Background and Aims: Parent–child interaction therapy (PCIT) is an evidence-based behavioral parent training program designed for preschool-age children that emphasizes supporting parent–child interaction patterns to improve child behavior and enhance the quality of parent–child relationships. PCIT has been deemed efficacious in treating children with disruptive behavior disorders, and recent studies have shown promising results utilizing aspects of PCIT with children with autism spectrum disorder (ASD), but none of these studies applied the entire PCIT intervention per manual protocol. The present study is the first to test the efficacy of PCIT, without modification, with families of preschool-age children with ASD without comorbid behavioral difficulties. Methods: This study employed a single-subject multiple-probe design to evaluate the efficacy of PCIT with four families with children with ASD between the ages of 2 and 4 years old ( M  = 40 months) over a 4-month period. Results: PCIT was effective in increasing positive parenting behavior, decreasing negative parenting behavior, and increasing child compliance to parental commands. Parents reported greater confidence in parenting abilities post-treatment and significant improvement in the core areas of autism symptomatology. Parents endorsed significant improvement in aspects of the parent–child relationship, such as attachment and involvement. Conclusions: Parents of children with ASD demonstrated more positive and effective parenting behavior and reported enhancements in the parent–child relationship after participating in PCIT. Children were more compliant to parental commands and exhibited improvements in social and behavioral functioning. Increases in positive parenting behaviors and child compliance to parental requests were maintained 1 month after treatment and outside the clinic setting during generalization sessions. Parents of children with ASD reported a high degree of satisfaction with PCIT. Implications: The present study provides initial evidence of the efficacy of utilizing PCIT with families of preschool-age children with ASD and supports the continued investigation of the efficacy of PCIT with this population.